ANALYSIS OF ECONOMIC LITERACY AND BUSINESS CAPITAL ON ENTREPRENEURIAL DECISIONS IN STREET VENDORS IN THE FIELD KAREBOSI MAKASSAR - Nasir, Nasir (jfpublisher, 2024)
Karebosi Square, Makassar, is one of the centers of economic activity that is a place for many street vendors (PKL) to run their businesses. In this context, entrepreneurial decisions are very important for street vendors to survive and develop in the midst of increasingly fierce competition. These decisions are often influenced by economic literacy and business capital, where economic literacy includes an understanding of financial management and business strategy, while business capital includes financial resources to start and run a business. This study aims to understand the influence of economic literacy and business capital on entrepreneurial decisions in street vendors in Karebosi Field, Makassar. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with 10 main informants, namely street vendors who have entrepreneurial experience in Karebosi Field. Field observations and documentation are also used to reinforce the data obtained. The data was analyzed using thematic analysis techniques to identify patterns and relationships between the variables studied. The results of the study show that economic literacy affects the way traders manage capital and face business challenges. A good understanding of economic literacy helps traders in making strategic decisions, such as capital allocation, cost control, and business development planning. In addition, access to business capital determines the ability of traders to start and maintain their business activities. This study concludes that economic literacy and business capital are key factors in entrepreneurial decision-making for street vendors.